The Impact of EURODAC in EU Migration Law: The Era of Crimmigration? - Benedita Menezes Queiroz (Market and Competition Law Review)
Counter-terrorism and public security measures have significantly altered EU immigration law. Under the premise that EU instruments which regulate EU immigration databases influence the legal regime of irregularity of migrants’ statuses, the present article argues that the latest developments in the area of data technology contribute to the phenomenon of “crimmigration”. This is so not only because they may generate a sort of “digital illegality” due to their impact on the categorisation of migrants, but also because they enable a conflation of treatment of irregularity, asylum seeking and criminality. This article focuses on the recent amendments and proposals for amendments to the EURODAC Regulation, a database that regulates the asylum fingerprint system in the EU. This is revealing of the ongoing broadening of the purpose of that data and law enforcement access to the collected information. The argument finds its basis in three main trends common to these databases: the erosion of the principle of purpose limitation, the widening of access to data by law enforcement authorities, and the digitalisation of borders through biometrics. Ultimately, this article claims that the level of surveillance of certain categories of migrants that may cross the borders of the EU puts at risk the distinction between illegally staying irregular migrants and criminals, given that the treatment of their personal data is insufficiently clear in practice.